Differential and interactional influence of socio-demographic variables on intellectual ability - Stella Eteng-Uket; Betty-Ruth Ngozi Iruloh (Journal of Pedagogical Research, 2023)
Intellectual ability, also known as intelligence, is a multifaceted construct that is typically measured through intelligence tests. The importance and complexity of intellectual ability have made it of significant interest to researchers and educators. This is coupled with the fact that it is one phenomenon that is influenced by a variety of factors. This prompted the study that sought to investigate the differential and interactional influences of gender, age, education, and ethnicity on intellectual ability in Rivers State Nigeria. The study employed the analytic descriptive survey design with a sample of 390 that was randomly drawn using a stratified sampling technique. A test of general reasoning ability, which is a standardized test, was used to elicit data on the variables of the study. Validity and high reliability coefficients were obtained for the instrument. Data were analysed using mean, standard deviation, t-test, one-way, and three-way ANOVA. The result showed that age and ethnicity had a significant influence on intellectual ability, but gender and educational level did not have a significant influence. Gender, age, and educational level did not have significant interactional influences as well. It was recommended that investing in education, particularly in the early years, can have lasting benefits for cognitive and intellectual ability development.